A multicenter post‐marketing evaluation of the Elixir DESolve® Novolimus‐eluting bioresorbable coronary scaffold system: First results from the DESolve PMCF study. Issue 6 (6th March 2018) - Nef, Holger; Wiebe, Jens; Boeder, Niklas; Dörr, Oliver; Bauer, Timm; Hauptmann, Karl‐Eugen; Latib, Azeem; Colombo, Antonio; Fischer, Dieter; Rudolph, Tanja; Foin, Nicolas; Richardt, Gert; et al.
Abstract: Objectives: To date, experience with bioresorbable scaffolds (BRS) that elute agents other than everolimus is limited. Thus, a post‐marketing clinical follow‐up study was conducted to evaluate the continued safety and effectiveness of the DESolve® NOVOLIMUS™ Eluting BRS as treatment for patients with stable coronary artery disease. Background: The DESolve BRS combines a poly‐l ‐lactide‐based backbone with a biodegradable polylactide‐based polymer and Novolimus, a macrocyclic lactone mTOR inhibitor. Methods: One hundred and two patients (mean age 62 years, 77.5% male) were enrolled at 10 European sites. Comparison of baseline and post‐procedural angiographic assessment was performed, and a device‐oriented composite endpoint (comprising cardiac death, target vessel myocardial infarction, and clinically driven target lesion revascularization) and rate of scaffold thrombosis at 12 months were examined. Results: The device was successfully delivered and deployed in 98.2% (107/109) of the lesions, with two failures to cross the lesion. A total of 100 patients (109 lesions) were treated with a DESolve BRS. Post‐procedural angiographic assessment indicated an in‐scaffold acute gain of 1.54 ± 0.44 mm, with a reduction in % diameter stenosis from 61.00 ± 11.29 to 12.69 ± 0.44. At 12 months, the device‐oriented composite endpoint had occurred in 3.0% (3/100) of patients, with 1.0% (1/100) experiencing scaffold thrombosis and myocardial infarction and 3.0% (3/100) undergoing target lesion revascularization. There were no cardiac deaths. Conclusions: Results through 12 months indicate that the DESolve BRS is a safe and effective treatment for coronary lesions, though larger, long‐term prospective studies are needed.